Znanja, stavovi i praksa perinatalnog i infantilnog oralnog zdravlja među zdravstvenim radnicima i studentima medicine i stomatologije - Lazarova, Aneta; Kokoceva Ivanovska, Olga; Gjorgievska, Elizabeta (Medicinska reč, 2024)
A shared approach, coordination, and care for oral health as an integral part of general health should be imperative for every primary healthcare worker. The purpose of this study is to evaluate the knowledge, attitudes, and practices regarding perinatal and infantile oral health in different groups of health professionals in North Macedonia. The survey was conducted from January 2020 to January 2021 with the distribution of an anonymous survey questionnaire electronically in the form of a Google Document to a different profile of healthcare professionals from primary healthcare in North Macedonia, as well as students of dentistry and medicine. The questions examined early childhood caries knowledge, attitudes about their role in preventing childhood oral health, and practices for promoting good oral health. It was determined that 85.7 percent of doctors believed they need additional oral health education, 93.9 percent of respondents believed that they must educate parents/guardians about the importance of the preventive measures to maintain children’s oral health and that they must advise parents in case of suspected caries to visit a dentist/pedodontist. Only 46.9% of respondents knew that cariogenic bacteria can be transmitted vertically from mother to newborn. A small percentage (26.5%) of respondents knew that white spots on baby teeth are early signs of caries. A Guide to Perinatal and Infant’s Oral Health for all health professionals who are in contact with a child in the first years of life would help to properly guide and educate parents in preserving infants` oral health.